Feeding by the nototheniid fish, Pagothenia borchgrevinki on the ice-associated copepod, Paralabidocera antarctica - Hoshiai, Takao; Tanimura, Atsushi; Fukuchi, Mitsuo; Watanabe, Kentaro (National Institute of Polar Research, 1989)
P(論文) More than 90% of food items in the stomach contents of the nototheniid, Pagothenia borchgrevinki were found to be copepods and copepod nauplii. Most of the nauplii was identified as Paralabidocera antarctica. As this copepod lived in the sea ice feeding on ice algae, it was concluded that there is a food chain, ice algae-P. antarctica-P. borchgrevinki in the Antarctic cryopelagic ecosystem. In feeding on nauplii, the fish preferred developed and larger individuals. departmental bulletin paper